Assessment of safety design and facilities at child care centre (Taska) / Mohd Azrul Azizan - Azizan, Mohd Azrul (Faculty of Architecture, Planning and Surveying, 2010)
Child Care Centre or Taska are the places where working parents send their children for oversee. In order to provide a better living, Child Care Centres should have high level of safety design facilities to prevent and decrease injury to the children. To get a clear picture of issues and problems related to Child Care Centre, an assessment has been carried out at six case studies which were Taska Rehal, Taska Si Cilik, Taska Nafis NDD, Taska Intan Ceria, Taska Permata PKPS and Taska Impian Cemerlan UiTM. The locations were selected around Shah Alam, Selangor Darul Ehsan. To achieve the objective, the assessment has been carried out using a checklist of guidelines taken from responsible bodies in Malaysia such as Local Authority, Welfare Community Department, Fire Bridget and Health Department to know whether the Child Care Centre complies with the existing safety requirements or not. Finally, the findings are calculated using the manual system. The percentage is defined from the overall data gain from assessment safety guidelines. Then, recommendations are given according the problems regarding the safety design facilities and how to improve in order to achieve the objective of better living for the children in Child Care Centre